Mathematical patterns in chemistry : on turn points in the molecular self-assemblage symmetry formation - Schulz, Lech P. (Array, 2009)
Summary: Does the abstract mathematics afford patterns for chemistry? It is supposed that mathematics has its own, autonomous criteria of development and that mathematical creativity cannot be progressed simply by a "blind" listing of possible tautologies. Simultaneously, applied findings in the independently developed mathematical areas are rather a rare case. In the present work, it has been shown that seemingly abstract and presumed not to have any direct application concepts of pure mathematics lead to the concrete entities encountered in chemistry. For these reasons, the general definition of molecular forms and mathematical atoms have been employed to derive objects corresponding to the basic particles of chemistry. Besides, using a pattern of foundations of arithmetic, a special relation has been found to determine such atomic species in some chemical categories. The arithmetical background of chemistry and possible extensions have been indicated in this way